ADIKTOLOGIE Journal 2019
DOI: 10.35198/01-2019-001-0001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Presumed IQOS Influencer Marketing on Instagram in the Czech Republic in 2018–2019

Abstract: BACKGROUND: Heated tobacco products (HTP) are novel electronic devices that produce an aerosol by heating modified tobacco. In July 2017, Philip Morris launched a heated tobacco product, IQOS, on the Czech market. The release of IQOS was promoted by a massive marketing campaign using various marketing channels. AIM: This paper presents an analysis of the influencers’ posts promoting a heated tobacco product (HTP), IQOS, produced by Philip Morris, in the Czech Republic. METHODS: Critical discourse analysis (CDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Our findings further refine the social media marketing presence of IQOS, which aligns with prior research that has documented and characterized emerging tobacco products across different social media platforms [15][16][17][18][19][20][23][24][25]33]. We found that promotional IQOS posts were largely driven by stakeholders along the IQOS business chain.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our findings further refine the social media marketing presence of IQOS, which aligns with prior research that has documented and characterized emerging tobacco products across different social media platforms [15][16][17][18][19][20][23][24][25]33]. We found that promotional IQOS posts were largely driven by stakeholders along the IQOS business chain.…”
Section: Discussionsupporting
confidence: 87%
“…A study found that on Instagram, the promotion of IQOS was overwhelmingly from online retailers and fan communities, featuring IQOS with terms of fashion, health, flavor, and cessation [23]. Another study in Czech found celebrities and influencers actively presented IQOS as a gateway to an aspirational, healthy, attractive, and celebrity lifestyle in their posts and videos since 2018 on Instagram [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PMI has been accused of advertising IQOS to youth and young adults, especially through social media 38. In Israel, recent repeated cross-sectional studies have shown a rise in IQOS experimentation among Jewish youth 39.…”
Section: Discussionmentioning
confidence: 99%
“…There are still some misperceptions of the risks of these products, mainly because of inaccurate information and sensational media headlines (O'Leary & Polosa, 2020). In addition, even some celebrities and influencers have been dynamically presenting IQOS in their posts and videos (Hejlová et al, 2019). The perceptions regarding IQOS were assessed through Twitter and included some positive feelings such as "IQOS is safer than cigarettes", or "IQOS helps quit smoking", with tweets expressing negative feelings.…”
Section: Perception Of the Dangerousness Of Htpsmentioning
confidence: 99%